Analisis Pengeluaran Pemerintah Terhadap Pembangunan Ekonomi Inklusif Pilar 1 di Provinsi Jawa Tengah - Faizin, M Ahsanul; prabowo, prayudi setiawan (Independent: Journal of Economics, 2023)
This study aims to examine the effect of government expenditure consisting of the realization of expenditure on economic functions, health functions and education functions on the inclusive economic development index of the pillars of economic growth and development. This study uses OLS analysis assisted by the Eviews 10 application. The research area is included in cross section data with a total of 35 districts and cities in Central Java in 2018. The results of the study are that economic function has no effect on PEI pillar 1, health function has no effect on PEI pillar 1, and educational function has a negative effect on PEI pillar 1. And simultaneously economic function, health function, and educational function have an effect on PEI pillar 1.